Prevalence of Digital Addiction among Medical Students in Iraq - F Al Shaikh, Suhaila; Abdulameer Abdulrasol, Zainab; Thaeer Abdulhakeem, Ameer; Tahseen Ahmed, Ahmed; Muhannad Hussein, Saif (South Asian Journal of Social Sciences and Humanities, 2025)
This study investigatesthe prevalence of smartphone addiction among medical college students in different Iraqi universities and its impact on academic performance, mental health, and physical well-being. A descriptive cross-sectional design was employed using an online self administered survey, distributed via social media from 14 February 2025 to 24 March 2025, which yielded responses from 673 participants from various institutions, predominantly from the University of Babylon. The sample included students from different medical specializations and different academic years, with a higher proportion of females (66.7%). The findings indicate a high prevalence of physical discomfort and psychological stress among users, as well as impaired academic performance and reduced engagement in social activities. Study recommends that educational institutions implement targeted awareness programs, promote digital detox initiatives, enhance counseling services, and consider policy interventions in academic settings. Moreover, future research employing longitudinal designs and objective usage metrics is needed to further elucidate the health implications of excessive smartphone use.